Exploratory gazes. Unpublished photographs of Asís Cabrero's Italian trip - María José Aldea Hernández; Iñaki Bergera (VLC Arquitectura)
As was the case in not just a few of his contemporaries, Francisco Cabrero's modern advent is centred on his initial trip, in this case the one made to Italy in 1941. The historiography of Spanish architecture in general and the specific studies on the architect have shown the impact and the scope of this two-month trip on his later career. Fleeing the ruling academicism in Spain, Cabrero 'discovers' in Italy the rationalist and abstract expression of monumentality. Nevertheless, the access to a wide photographic reportage —unpublished up to now— accomplished by the architect during the trip, allows us to document his journey but also to put in to question those claims. The photographs introduce us for the first time to Cabrero the photographer —to his particular way of constructing an image— and as a result they pave the way for the recognition of this visual tool as an exploratory instrument of the gaze to the detriment of the pencil and notebook. Above all and paradoxically, they contradict the supposed fascination for modern language in Cabrero since discovering that historical architecture was almost the only objective of his selective photographic look and as a result, the primary source, of his transforming inspiration.